The home court advantage: Evidence from men`s college basketball - Yi, D. T. (The Sport Journal, 2017)
The home court advantage in team sports is a well-established phenomenon whose true causes are not yet fully known despite the varying range of theories. In this paper, the researcher employs a stochastic production frontier model and explains the home court advantage phenomenon as an efficiency-enhancing phenomenon. Home teams, when supported by the home team`s crowd, play better with enhanced game efficiency. It is not simply playing aggressively at home or the familiarity of the home court that gives the home teams advantage over visiting teams, but rather the home court atmosphere enhances the home teams to play up to their potential.